The influence of flexion distraction spinal manipulation on patients with lumbar spinal stenosis: A prospective, open-label, single-arm, pilot study. (October 2022) - Smith, Dean L.; Olding, Kurt; Malaya, Christopher A.; McCarty, Matthew; Haworth, Joshua; Pohlman, Katherine A.
Abstract: Objective: Evaluate chiropractic care including flexion distraction spinal manipulation for improving function, symptoms and performance-based mobility in patients with lumbar spinal stenosis (LSS) using a pretest-posttest design. Methods: Data were collected at baseline, midpoint and final visits prior to care on each visit. Objective data included Timed Up and Go, Five Times Sit to Stand, and balance (force plate). An additional balance assessment was also conducted after care on the baseline visit. Subjective data included: Activities-Specific Balance Confidence Scale, Zurich Claudication Questionnaire, and pain ratings. Balance data were securely transferred via iDrive; the others were collected via REDCap. Results: Twelve patients (mean age = 83.5 years ± 5.71) completed the average midpoint visit at 9 visits and the final visit at 13.7 visits. Timed Up and Go and Five Times Sit to Stand Test decreased by 5.2 and 6.7 s at midpoint and 5.4 and 5.7 s at the final visit, respectively compared to the baseline visit (p < 0.05). Baseline visit pre-post reductions were found in anterior-posterior sample entropy and mean frequency of postural sway (p < 0.05). No balance change was found between baseline and mid or final visits. All subjective measures had statistically and clinically meaningful improvement. Conclusion: Significant improvement in objective and subjective outcomes were found after a pragmatic course of care including spinal manipulation in LSS patients.